Buku saku kanker serviks untuk meningkatkan pengetahuan tentang deteksi dini kanker serviks pada WUS - Hesty Widyasih (Jurnal Kesehatan Pengabdian Masyarakat (JKPM), 2020)
WHO estimates that 500,000 new cases of cervical cancer are diagnosed with around 3,750 deaths per year. One of the efforts to reduce cervical cancer is early detection (IVA/Papsmear). Public awareness to conduct early detection needs to be sought by disseminating information about the dangers of cervical cancer. One effort that can be done is to provide health education to Fertile Age Women (WUS), which is a risk group for cervical cancer. The use of pocket books is one alternative media to deliver messages about early detection of cervical cancer. The purpose of the activities is to increase knowledge about early detection of cervical cancer. The method is community education with counseling to increase understanding and awareness about early detection of cervical cancer by using a pocket book. Participants were 50 women in Suryodiningratan Urban Village, Yogyakarta City. Characteristics of participants are mostly over 35 years old, have 2-3 children, have a high school education and are not working (Housewife). The level of knowledge about early detection of cervical cancer is mostly good. The results of the activity showed an increase in the number of partisipants with good knowledge about early detection of cervical cancer before and after the use of a pocket book. Pocket books can be an alternative for health promotion about early detection of cervical cancer.